ANALISIS INTERFERENSI MORFOLOGI PADA HASIL TULISAN KARANGAN MAHASISWA PEMBELAJARA BAHASA JEPANG - Rizka Auliana; Yuniarsih; Cut Erra Rismorlita (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
This research focused on morphological interference in Jakarta State University student‟s composition. This research aimed to analyze the type of morphological interference in composition and its effect to the student‟s composition. Student‟s composition were taken from two composition classes of first year Japanese Language major student on their second term. The type of morphological interference that analyzed in this research are divided into three types: Function of morphemes and likelihood of transfer, Replica functions of equivalent morphemes, and Abandonment of obligatory distinction. Meanwhile, the effect of morphological interference are Less Production, Added Production, Wrong Production, and Wrong interpretation.